2014
DOI: 10.1002/smll.201303677
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Dynamics of Glucocorticoid Receptor at the Plasma Membrane of Activated Mast Cells

Abstract: In addition to their actions in the cell nucleus, glucocorticoids exhibit rapid non-nuclear responses that are mechanistically not well understood. To explain these effects, the localization of a glucocorticoid receptor (GR) expressed in mast cells as a GFP fusion was analyzed after activation of the cells on allergenic lipid arrays. These arrays were produced on glass slides by dip-pen nanolithography (DPN) and total internal reflection (TIRF) microscopy was used to visualize the GR. A rapid glucocorticoid-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Here, it has been shown that following allergen-mediated crosslinking of FcεRI of mast cells, the GR is rapidly recruited to the plasma membrane ( Fig. 9.1 ) and this process is further transiently enhanced by glucocorticoid treatment [ 52 ]. It therefore appears that the membrane-localized GR may serve as an early sensor for the hormone to amplify its main genomic action [ 52 ].…”
Section: Mast Cellsmentioning
confidence: 90%
See 3 more Smart Citations
“…Here, it has been shown that following allergen-mediated crosslinking of FcεRI of mast cells, the GR is rapidly recruited to the plasma membrane ( Fig. 9.1 ) and this process is further transiently enhanced by glucocorticoid treatment [ 52 ]. It therefore appears that the membrane-localized GR may serve as an early sensor for the hormone to amplify its main genomic action [ 52 ].…”
Section: Mast Cellsmentioning
confidence: 90%
“…9.1 ) and this process is further transiently enhanced by glucocorticoid treatment [ 52 ]. It therefore appears that the membrane-localized GR may serve as an early sensor for the hormone to amplify its main genomic action [ 52 ]. In kinetic studies of hormonedependent nuclear translocation of the GR, a transient delay in the mobility of the GR was observed in allergen-activated compared to non-activated mast cells [ 52 ].…”
Section: Mast Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…different inks written at the same time and in close vicinity on the surface) functionalization of surfaces with biomimetical membrane stacks used e.g. in 3 immunological assays [29][30][31][32]. This technique does not rely on a specific surface chemistry and can therefore be applied to various substrates, e.g.…”
mentioning
confidence: 99%